Development of a novel electrospun nanofibrous delivery system for poorly water-soluble β-sitosterol - Urve Paaver; Ivo Laidmäe; Hélder A. Santos; Jouko Yliruusi; Jaan Aruväli; Karin Kogermann; Jyrki Heinämäki (Elsevier, 2016)
Electrospinning was used as a novel technique for fabricating polymeric nanofibers of a serum cholesterol lowering and poorly water-soluble plant sterol, β-sitosterol. Chitosan was used as a stabilizer/carrier polymer. The mean diameters of nanofibers ranged from 150 nm to 218 nm. β-sitosterol was in an amorphous form and homogeneously dispersed in the nanofibers. The β-sitosterol-loaded nanofibers were freely water-soluble and exhibited very short lag-time in releasing the plant sterol. The dissolution was associated with an immediate recrystallization of β-sitosterol in submicron level. In conclusion, electrospinning is a promising future technology for the formulation of poorly water-soluble plant sterols.